New atheism and its enemy - Sieczkowski, Tomasz (Hybris, 2012)
The popularity of New Atheism in the market of ideas in the last decade is unprecedented. This informal movement introduced radical atheism into the mainstream of public considerations and created a massive resentment amongst philosophers and theologians. Many critiques come predictably from conservative groups, which makes them conventional. But lately also the left-wing thinkers began to turn to religion and its emancipation potential. One of the prominent left-wing thinkers, Terry Eagleton, proposed a wholesale critique of New Atheism in his Reason, Faith, and Revolution. Reflections on the God Debate (2009). What I’m trying to do in this paper is to critically compare his animosity towards New Atheism with his positive project of rehabilitation of an orthodox Christianity, the latter being a means towards realizing Eagleton’s political agenda. This agenda is, I presume, based on theological if not metaphysical notions and sentiments.